Learning Media Based on Local Wisdom Using 3D Augmented Reality Technology to Increase Student Interest in Learning - Isro'ullaili; Fakhrur Rassyi, Sultan; Haryanto; Iqbal A. (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2024)
Advances in information and communication technology (ICT) have brought significant changes to the world of education. One innovation that is increasingly being implemented is the use of learning media based on augmented reality (AR) technology. This development research aims to produce learning media based on local wisdom with augmented reality (AR) technology that is feasible, practical and effective in increasing students' interest in learning. This research uses the ADDIE model with five stages, namely Analysis, Design, Development, Implementation and Evaluation. Research carried out at SMAN includes validation of media and materials by experts, teacher assessments, and student responses. This research uses an experimental class and a control class to compare the effectiveness of the media. Data collection includes validation sheets, teacher assessments, student responses, and questionnaires measuring interest in learning, with data analysis using the t-test. The research results show that AR-based learning media is considered feasible. Based on the t test, there is a significant difference between the experimental class and the control class. This shows that AR media is effective in increasing student interest, and it is recommended to further improve this media. The implications of this research provide alternative learning methods that are more innovative and contextually based, so that they can increase students' motivation and interest in learning.